Prevalence and determinants of motor stereotypies in autism spectrum disorder: A systematic review and meta-analysis - Melo, C (2020)
Stereotypies are frequently reported in people with autism spectrum disorder (ASD) but remain one of the less explained phenomena. We aimed to describe, through a systematic review and a meta-analysis, the prevalence of motor stereotypies in ASD and study the factors that influence this prevalence. Our literature search included MEDLINE, Scopus, and PsycINFO databases. Quality and risk of bias were assessed. Thirty-seven studies were included and the median prevalence of motor stereotypies in ASD was 51.8%, ranging from 21.9% to 97.5%. The most frequent determinants associated with a higher number of stereotypies in ASD were a younger age, lower intelligence quotient, and a greater severity of ASD. Moreover, gender did not seem to influence the prevalence of stereotypies. Meta-analytic analysis showed that lower IQ and autism diagnosis (independent of IQ) are associated with a higher prevalence of motor stereotypies (odds ratio = 2.5 and 4.7, respectively). Limitations of the reviewed literature include the use of convenience samples, with small sizes and heterogeneous inclusion criteria, and the predominance of high-functioning autism individuals.